Prinsip Perencanaan Kurikulum dalam Meningkatkan Mutu Pendidikan: Kajian Literatur - Ice Rosina Sari; Agus Pahrudin; Sri Rahma (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
Curriculum planning is a strategic component of educational quality because it determines how institutional vision, graduate profiles, learning outcomes, content structure, pedagogical strategies, assessment systems, and quality assurance mechanisms are translated into meaningful learning experiences. This study aims to analyze the principles of curriculum planning in improving educational quality through an integrative literature review. The study synthesized peer-reviewed articles published between 2018 and 2025 that were relevant to curriculum planning, curriculum management, quality assurance, outcome-based education, educational quality culture, and continuous improvement. The literature was analyzed through data reduction, thematic coding, conceptual comparison, and synthesis of findings. The results show that quality-oriented curriculum planning is constructed through seven main principles: relevance, coherence, participation, flexibility, integration, learning outcome orientation, and continuous evaluation. Relevance ensures that the curriculum responds to learners’ needs, societal demands, scientific development, labour market expectations, and institutional identity; coherence aligns vision, graduate profiles, learning outcomes, content, pedagogy, and assessment; participation strengthens accountability and stakeholder ownership; flexibility enables curriculum adaptation to technological, social, and policy changes; integration connects knowledge, skills, attitudes, values, and learning experiences; learning outcome orientation makes curriculum implementation measurable; and continuous evaluation supports evidence-based improvement. This study concludes that curriculum planning should not be treated merely as an administrative document, but as a strategic quality instrument that influences educational input, process, output, outcome, and institutional quality culture. The implication of this study is that educational institutions need to develop curriculum planning systems that are data-driven, participatory, coherent, adaptive, and continuously evaluated to ensure sustainable improvement in educational quality.